Synthesis and phase-transition behaviors of new symmetrical dimer liquid crystals containing benzothiazole unit. (1st February 2017) - Foo, Kok-Leei; Seou, Chi-Kien; Ha, Sie-Tiong; Lee, Siew-Ling; Yeap, Guan-Yeow
ABSTRACT: This article reports the synthesis and characterization of a series of homologous symmetrical dimers α, ω-bis[4-(6′-ethoxybenzothiazol-2′-yl)iminomethylphenoxy]alkane. Five members with different lengths of alkyl spacer groups of even parity varying from butyl (C4 H8 ) to dodecyl (C12 H24 ) were synthesized. Spectroscopic analysis (IR, 1 H and 13 C NMR) along with electron-ionization mass spectrometric techniques were employed to verify the molecular structures of the dimers. Differential scanning calorimeter was used for determination of the phase-transition temperature and associated enthalpy changes. Optical studies and mesophase identification were carried out using a polarizing optical microscope attached to hotstage. A diversity of phase-transition behavior was observed as the length of the alkyl spacer increased from C4 H8 to C12 H24 . Almost all title compounds exhibited nematic phase except the dimer containing butyl spacer in which the mesomorphic property was absent.